“Hapolas” Kearifan Budaya Lokal Masyarakat Pesisir Pulau Makian Dalam Merawat Harmoni Kemanusiaan - Ali Lating; Fathnun Tan (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2023)
Abstrak Local community cultural wisdom is a noble culture resulting from thoughts that are born from noble, intelligent and innovative awareness to answer needs in various aspects of life. As a way of life, local cultural wisdom is very important because it can maintain the harmony of human continuity, care for the relationship between humans and the Divine Nature as well as with the environment. Local wisdom disciplines all parties to maintain the sustainability of living space. This research tries to describe how the local culture of the Makian island coastal community cares for human harmony. Through the hapolas culture, ancestral values ​​that guide life until now are still going well.